Physiological Changes and Time-Course Transcriptomic Analysis of Salt Stress in Chenopodium quinoa - Li, Peipei; Zhang, Yemeng (Biology (Basel, Switzerland), 2025)
Quinoa, a halophytic pseudocereal crop, is highly resistant to harsh growing environments and is considered a suitable crop for cultivation in marginal areas. The germination period plays a decisive role in the formation of the crop population and the growth and development of quinoa, but our understanding of the regulatory mechanism of salt stress remains limited. In this study, we investigated the physiological changes and mechanisms of tolerance response to salt stress in quinoa seedlings. The results showed that salt stress severely reduced the growth of quinoa seedlings. Moreover, salt stress increased the H2O2 level in the seedlings, thereby aggravating lipid peroxidation of the cell membrane and consequently increasing MDA content. Meanwhile, the antioxidant enzyme activities such as POD, SOD, GR and GPX of seedlings were enhanced in response to salt stress, which was consistent with the results of the RNA-sequencing. These results suggest that the increase in antioxidant enzyme activities in quinoa seedlings attenuates the ORS imbalance caused by salt stress. In addition, we identified 69, 40, 120 and 47 key genes in the “photosynthesis”, “glutathione metabolism”, “phenylpropanoid biosynthesis” and “starch and sucrose metabolism” pathways, respectively. Moreover, the predicted 235 transcription factors involved in the salt stress response have various hormone cis-elements in their promoter regions, which also indicates that multiple hormones are involved in the salt stress response process in quinoa. Therefore, we hope that these genes and mechanisms will provide some basis for understanding salt tolerance in quinoa.